2022
DOI: 10.3389/fnut.2022.881865
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Baking Process on the Chemical Composition, Sensory Quality, and Bioactivity of Tieguanyin Oolong Tea

Abstract: Tieguanyin oolong tea (TOT), a semi-oxidized tea originating from Anxi county in China, is categorized into jade TOT, medium-baked TOT, and deep-baked TOT, based on different baking processes. To study the effects of baking, chemical analysis, sensory evaluation, and bioactivity assessments of the three TOTs were conducted. The results indicated that the baking process promoted the formation of colored macromolecules (e.g., theabrownins), which affected the color of tea infusion. Free amino acids underwent the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…The content of fructose was insignificantly different. Soluble polysaccharides, which were macromolecules contributing to the thick taste of tea infusions and displayed multiple bioactivities such as antioxidant and α-glucosidase inhibitory activity ( 18 , 22 ), were observed in tea flowers, ranging from 12.4 to 16.2 mg/g ( Table 1 ). Yujinxiang had a higher content of soluble polysaccharides compared with the other three.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The content of fructose was insignificantly different. Soluble polysaccharides, which were macromolecules contributing to the thick taste of tea infusions and displayed multiple bioactivities such as antioxidant and α-glucosidase inhibitory activity ( 18 , 22 ), were observed in tea flowers, ranging from 12.4 to 16.2 mg/g ( Table 1 ). Yujinxiang had a higher content of soluble polysaccharides compared with the other three.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrahigh performance liquid chromatography-Q Exactive-Orbitrap-mass spectrometry (UPLC-QE-Orbitrap-MS) was used to determine the composition of procyanidins, organic acids, flavonols, methylxanthines, and saponins, based on published methods with modifications ( 11 , 18 ). The separation was performed on an ACQUITY UPLC BEH C18 column (1.7 μm, 2.1 mm × 100 mm, Waters, Milford, MA, United States) using a Dionex Ultimate 3,000 RS system.…”
Section: Methodsmentioning
confidence: 99%
“…Non-targeted metabolomics analysis was carried out using UPLC-HRMS (Q-Exactive system, Thermo Fisher Scientific, Rockford, IL), as described previously (25) with some modifications. The column was an Acquity UPLC BEH C18 (100 nm × 2.1 mm; 1.7 µm, Waters, Manchester, UK).…”
Section: Non-targeted Metabolomics Analysismentioning
confidence: 99%
“…During this step, tea leaves were repeatedly roasted over smoldering charcoal at high temperature (usually 120–150°C) for a long period of time, and the composition as well as contents of metabolites varied significantly. Numerous studies has revealed that high temperature roasting induced the epimerization of (2 R ,3 R )‐epicatechins to (2 S ,3 R )‐catechins, the degradation of galloylated catechins to non‐galloylated catechins, and the interaction of catechins with amino acids ( e.g ., theanine) or monosaccharides ( e.g ., glucose), which caused the large fluctuation of these metabolites and the formation of some adducts such as N ‐ethyl‐2‐pyrrolidinone substituted flavan‐3‐ols (EPSFs) and 6/8 C glucose substituted EGCG (Cao et al., 2021; Gao et al., 2022; Guo, Ho, Schwab et al., 2021; Jiang et al., 2023; Jiang, Han et al., 2021; Peng, Dai et al., 2022; Zhou, Wu et al., 2019). Furthermore, roasting temperature dominated the direction of catechins response, for example, higher level of GCG was found in tea leaves roasted under higher temperature (145–150°C) while higher levels of EGC, gallocatechin, and GA were found in tea leaves roasted under relative lower temperature (120–130°C) (Guo, Ho, Schwab et al., 2021; Jiang, Han et al., 2021).…”
Section: Applications Of Metabolomics In Tea Studiesmentioning
confidence: 99%
“…(2021) compared the volatile differences between Wuyi Rock teas under different roasted degrees by GC‐O‐MS and GC × GC‐O‐MS, and results showed that moderate roasted (fired) and high roasted teas had similar aroma profile with a gradually increased levels of Strecker aldehydes, esters, heterocycles, and terpenes. Furthermore, the main aroma‐active substances in the highly/heavy roasted teas were found to be 2‐ and 3‐methylbutanal, furaneol, 3‐methylbutanoic acid, propanoic acid, methional, β‐myrcene, 2‐pentylfuran, 5‐ and 6‐methyl‐2‐ethylpyrazine, 2‐ethyl‐3,5‐dimethylpyrazine, 3,5‐diethyl‐2‐methylpyrazine, 5‐hydroxymethylfurfural, and furfural, which contributed to the roasted, woody, burnt/smoky, and cinnamon‐like scents (Gao et al., 2022; Guo, Ho, Schwab et al., 2021; Guo, Ho, Wan, et al., 2021; Lan et al., 2022). Hexanal, linalool, ( Z )−3‐hexen‐1‐ol, ( Z )−4‐heptenal, ( E )−2‐heptenal, geraniol, pentanal, and nerolidol were in charge of the relative low temperature roasted tea's flowery, fruity, and grassy/fresh leaf‐like scents (Yang, Yu et al., 2022).…”
Section: Applications Of Metabolomics In Tea Studiesmentioning
confidence: 99%